The Effect of Financial Literacy, Income, and Lifestyle on Financial Management with Locus of Control as an Intervening Variable in Employees PT Alfa Scorpii Main Dealer Medan - Natasya Miranda Puteri; Noni Ardian; Maya Macia Sari (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of Financial Literacy, Income, and Lifestyle on Financial Management with Locus of Control as a mediating variable in employees of PT Alfa Scorpii Main Dealer Medan. This study uses a quantitative method with a causal associative approach. The study population was all contract employees of the operation section totaling 40 people, and used saturated sampling techniques. The data analysis technique used Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS software. The results of the study show that: Lifestyle has a positive and significant effect on the Locus of Control and Financial Management; Financial Literacy has a positive and significant effect on the Locus of Control and Financial Management; Revenue has a positive and significant effect on the Locus of Control and Financial Management; Financial Management has a positive and significant effect on the Locus of Control. The results of the mediation test showed that Financial Management was able to mediate the influence of Lifestyle on the Locus of Control and Income on the Locus of Control, but was unable to mediate the influence of Financial Literacy on the Locus of Control. The R-Square value shows that independent variables are able to explain Locus of Control by 56.4% and Financial Management by 35.5%, with a Q² value of 0.719 which indicates that the model has strong predictive relevance. This study concludes that Financial Literacy, Income, and Lifestyle are important factors that affect employee Financial Management, and Financial Management plays a role as a partial mediator in increasing the Locus of Control of employees of PT Alfa Scorpii Main Dealer Medan. An abstract is often presented separate from the article, so it must be able to stand alone. A well-prepared